Table 4_TCR repertoire of human cytotoxic CD4 T cells responding to betaherpesviruses HHV-6B and HCMV.xlsx - Aniuska Becerra-Artiles (829447) (2025)
Background The role of CD4 T cells in the control of viral infections beyond their traditional helper activity has been increasingly recognized, and CD4 T cells with cytotoxic capacity have been reported for the nearly ubiquitous betaherpesviruses HCMV (human cytomegalovirus) and HHV-6B (human herpesvirus 6B). Objective We sought to investigate the functional landscape of cytotoxic CD4 T cells responding to HHV-6B and HCMV epitopes presented by DRB1*03:01 and to identify public T-cell receptors (TCRs) (i.e., shared by multiple subjects). Approach We tetramer-sorted epitope-specific CD4 T cells from healthy donors and performed RNA and TCR sequencing to assess functional profiles and identify TCR clonotypes. We evaluated the publicity of the repertoire and tested the functionality, epitope specificity, and sensitivity of selected public clonotypes. Results Differential gene expression analysis comparing T cells expanded with HHV-6B and HCMV epitopes showed differences in their functional profiles, with the HCMV-expanded T cells displaying a more robust cytotoxic gene expression signature. Tens to hundreds of TCR clonotypes responding to HHV-6B or HCMV were identified in each subject. The TCR repertoires were dominated by private clonotypes in all subjects, but 3 public TCRα/β, along with 41 public TCRα and TCRβ clonotypes were identified. Some of these clonotypes and closely related variants were found in a substantial fraction of DRB1*03:01 subjects in datasets of total peripheral blood TCR repertoires. TCRs associated with two HHV-6B epitopes (U11.306–323 and U85.88-104) and one HCMV epitope (pp65.509-523) were cloned for validation and biochemical characterization. Using an in vitro activation assay, the epitope specificity was confirmed for each selected TCRα/β, with half-maximal activation observed at 5–50 nM peptide concentration. With one exception, all TCRs bound tightly to the corresponding peptide-major histocompatibility complex (pMHC) tetramer. Finally, minimal peptide mapping combined with structural modeling of pMHCs identified potential sites of TCR interaction. Conclusions CD4 T cells recognizing HHV-6B or HCMV exhibit cytotoxic signatures and can lyse antigen-pulsed target cells, with the HCMV-specific population exhibiting greater activity. The TCR repertoires of CD4 T cells recognizing HHV-6B or HCMV epitopes presented by DRB1*03:01 are broad but include public TCR clonotypes. These TCRs may be useful to monitor infection, reactivation under immunosuppressive conditions, and response to therapy.